The GA-Hecate Peptide inhibits the ZIKV Replicative Cycle in Different Steps and can Inhibit the Flavivirus NS2B-NS3 Protease after Cell Infection - Sanches, Paulo Ricardo da Silva [UNESP]; Faria, João Caldana Elias de Campos [UNESP]; Bittar, Cíntia [UNESP]; Olivieri, Hugo Alexandre Siqueira Guberovich [UNESP]; Mesquita, Nathalya Cristina de Moraes Roso; Noske, Gabriela Dias; de Godoy, Andre Schutzer; Oliva, Glaucius; Rahal, Paula [UNESP]; Cilli, Eduardo Maffud [UNESP] (Bentham Science Publishers, 2024)
Background: Peptide drugs are advantageous because they are subject to rational design and exhibit highly diverse structures and broad biological activities. The NS2B-NS3 protein is a particularly promising flavivirus therapeutic target, with extensive research on the development of inhibitors as therapeutic candidates, and was used as a model in this work to determine the mechanism by which GA-Hecate inhibits ZIKV replication. Objective: The present study aimed to evaluate the potential of GA-Hecate, a new antiviral developed by our group, against the Brazilian Zika virus and to evaluate the mechanism of action of this compound on the flavivirus NS2B-NS3 protein. Methods: Solid-phase peptide Synthesis, High-Performance Liquid Chromatography, and Mass Spectrometry were used to obtain, purify, and characterize the synthesized compound. Real-time and enzymatic assays were used to determine the antiviral potential of GA-Hecate against ZIKV. Results: The RT-qPCR results showed that GA-Hecate decreased the number of ZIKV RNA copies in the virucidal, pre-treatment, and post-entry assays, with 5-to 6-fold fewer RNA copies at the higher nontoxic concentration in Vero cells (HNTC: 10 μM) than in the control cells. Enzymatic and kinetic assays indicated that GA-Hecate acts as a competitive ZIKV NS2B-NS3 protease inhibitor with an IC50 of 32 nM and has activity against the yellow fever virus protease. Conclusion: The results highlight the antiviral potential of the GA-Hecate bioconjugate and open the door for the development of new antivirals.
Keywords: bioconjugate; flavivirus; NS2B-NS3; peptides; protease; Zika virus